1999
DOI: 10.1002/1531-8249(199905)45:5<668::aid-ana19>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and subcellular localization of parkin protein: Absence of protein in autosomal recessive juvenile parkinsonism patients

Abstract: Autosomal recessive juvenile parkinsonism (AR‐JP) is a distinct clinical entity characterized by a selective degeneration of nigral neurons. Recently, the parkin gene responsible for AR‐JP has been identified. Now, we report the subcellular localization of Parkin protein in patients with AR‐JP or Parkinson's disease (PD) and in controls by immunoblotting and immunohistochemistry using antibodies raised against the Parkin molecule. Parkin protein was absent in all regions of the brains of patients with AR‐JP. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
181
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(203 citation statements)
references
References 12 publications
18
181
1
3
Order By: Relevance
“…As is the case in conventional idiopathic PD, the neuropathologic changes of parkin-linked AR-JP are largely confined to the brain stem and include the loss of selected neurons and local gliosis. However, ␣-synuclein-and ubiquitin-positive neuronal inclusions, LBs, are generally absent in parkin-linked AR-JP (11)(12)(13).…”
supporting
confidence: 58%
“…As is the case in conventional idiopathic PD, the neuropathologic changes of parkin-linked AR-JP are largely confined to the brain stem and include the loss of selected neurons and local gliosis. However, ␣-synuclein-and ubiquitin-positive neuronal inclusions, LBs, are generally absent in parkin-linked AR-JP (11)(12)(13).…”
supporting
confidence: 58%
“…The main histopathological difference between patients with parkin mutations and those with sporadic PD are the absence of Lewy bodies (despite Chen et al 2000) and the restriction of neuronal loss to the substantia nigra and locus caeruleus in patients with parkin mutations (Mori et al 1998). Pathological studies of the brains of patients with AR-JP showed absence of parkin protein (Shimura et al 1999). It has been hypothesized that accumulation of (as yet unidentified) proteins causes selective neuronal cell death in AR-JP without formation of Lewy bodies.…”
Section: Parkin (Gene Locus Park2 Omim 602544)mentioning
confidence: 71%
“…DISCUSSION The recessive heritability of Parkinson's disease caused by parkin gene lesions underscores the importance of parkin function for the survival of the dopaminergic neurons of substantia nigra pars compacta and suggests that its dysfunction can contribute to the disease progression in sporadic Parkinson's disease. This is corroborated by the detection of cleaved parkin fragments in substantia nigral tissue affected by Parkinson's disease and in Lewy bodies isolated from diseased tissue (30,31). Moreover, proteolytic inactivation of parkin may play a broader role in neurodegenerative settings as recently demonstrated by parkin's rapid catabolism upon hypoxia (32).…”
Section: Endogenous Caspase-8 But Not Endogenous Caspase-3 Cleaves mentioning
confidence: 99%